Development of skills for life in mobile school: strategy for the empowerment of children and adolescents as subjects of right - Chaves-Oviedo, Maria Lizzeth; Dorado-Martinez, Alvaro Darío (Universidad y Salud, 2019)
Introduction: Life skills are a set of characteristics that allow individuals to act properly in a daily manner, facilitating an appropriate physical, emotional and intellectual development. Objective: To empower children and adolescents as subjects of rights, through the strengthening of life skills. Materials and methods: A qualitative paradigm with an action-research approach that developed a mobile school strategy which included a series of workshops with 20 children and adolescents whose ages ranged between 6 and 14 years. Results: Children and young people acquired and strengthened a behavioral repertoire in defense of their childhood and also engaged in community activities. Conclusions: Mobile School empowered children and adolescents as subjects of rights, who cleraly recognized their fundamental rights and duties and also actively and constantly participated in the community reality.